Bibliometric Analysis: Trends And Contributions of Research in The Field of Artificial Intelligence - Febriansyah, Donny; Alsaud, Abdal Azis (West Science Interdisciplinary Studies, 2024)
This research aims to investigate research developments and research contributions in the field of Artificial Intelligence (AI) through a bibliometric analysis approach. Bibliometric data is obtained from various scientific reference sources including journal articles, conferences and books within a certain time period. The results of the analysis show an exponential growth in AI publications over the last few years. This study also identified a trend of strong research collaboration between researchers and research institutions in AI development. Dominant research topics include machine learning, natural language processing, image recognition, and robotics. Additionally, the study identifies the most prolific authors in the discipline and measures research impact based on the number of citations received. The results of this research provide deep insight into developments in AI research, enabling stakeholders to understand current research trends and focus. These findings can also serve as a guide for future research directions in the field of Artificial Intelligence.